Anaerobic co-digestion of swine wastewater and kitchen refuse: effect of pre-treatment on substrate solubilization & biodegrability - Đặng, Trung Hiếu (2020)
Establish operation guideline to define Biomethane Potential (BMP) of substrates using respirometer equipment. Determine Biological Methane Potential (BMP) of swine slurry and three kinds of kitchen refuse in separate and co-digestion mode. Evaluate the effect of Thermal and Peracetic acid pre-treatment on co-substrate solubilization and biodegradability, associated with correspondingkinetic constants.